The Effectiveness of Government Policy on the Mental Health of Toxic Relationship Victims - may, nazwa; Handayani, Trini; Amalia, Mia; Mulyana, Aji (Jurnal Ilmiah Kesehatan, 2024)
Toxic relationships can manifest in various connections between partners, friends, colleagues, and even family members. These detrimental relationships have the potential to disrupt individuals' mental health, well-being, and productivity. Therefore, the government must implement substantial policies to address this issue and make individuals aware of its severity to mitigate negative stigmas. This research aims to assess how toxic relationships impact the mental health of first-semester students at the Faculty of Law, Suryakancana University. It is anticipated that the findings of this research will offer valuable insights for government development of preventive and intervention strategies. Additionally, this study seeks to raise public awareness regarding the significance of maintaining healthy relationships and the adverse effects of toxic relationships on mental health. Through this increased awareness, it is hoped that the stigma associated with mental health disorders will diminish, and individuals will be more inclined to seek assistance when needed. The research employs both qualitative and quantitative methods.